Reduction in the Reverse-Bias Effect by an Abrupt Break in the Sequential Regularity of Visual Events. (April 2016) - Urakawa, Tomokazu; Hirose, Nobuyuki; Mori, Shuji
A bistable image is more likely to be initially perceived as the reversal of its preceding unambiguous version presented for a prolonged period. This perceptual bias is called the reverse-bias effect . We hypothesized that an abrupt break in the sequential regularity of visual events, synchronized with the onset of a bistable image, counteracts the reverse-bias effect in a similar manner to the disturbing effect of noise in the perceptual process. Under the condition in which the reverse-bias effect was achieved with the Necker lattice, the orientation of the bars around the lattice was simultaneously changed at the onset of the lattice, yielding an abrupt break in the sequential regularity of visual events besides the lattice. The results obtained showed that the reverse-bias effect was significantly reduced by the abrupt break, suggesting that an abrupt break in the sequential regularity of visual events perturbs the perceptual bias of the bistable image, similar to that caused by noise.